Genomic single-nucleotide polymorphisms confirm that Gunnison and Greater sage-grouse are genetically well differentiated and that the Bi-State population is distinct. (29th April 2015) - Oyler-McCance, Sara J.; Cornman, R. Scott; Jones, Kenneth L.; Fike, Jennifer A.
Abstract: Sage-grouse are iconic, declining inhabitants of sagebrush habitats in western North America, and their management depends on an understanding of genetic variation across the landscape. Two distinct species of sage-grouse have been recognized, Greater ( Centrocercus urophasianus ) and Gunnison sage-grouse ( C. minimus ), based on morphology, behavior, and variation at neutral genetic markers. A parapatric group of Greater Sage-Grouse along the border of California and Nevada ("Bi-State") is also genetically distinct at the same neutral genetic markers, yet not different in behavior or morphology. Because delineating taxonomic boundaries and defining conservation units is often difficult in recently diverged taxa and can be further complicated by highly skewed mating systems, we took advantage of new genomic methods that improve our ability to characterize genetic variation at a much finer resolution. We identified thousands of single-nucleotide polymorphisms (SNPs) among Gunnison, Greater, and Bi-State sage-grouse and used them to comprehensively examine levels of genetic diversity and differentiation among these groups. The pairwise multilocus fixation index ( F ST ) was high (0.49) between Gunnison and Greater sage-grouse, and both principal coordinates analysis and model-based clustering grouped samples unequivocally by species. Standing genetic variation was lower within the Gunnison Sage-Grouse. The Bi-State population was also significantly differentiated from Greater Sage-Grouse, albeit more weakly ( F ST = 0.09), and genetic clustering results were consistent with reduced gene flow with Greater Sage-Grouse. No comparable genetic divisions were found within the Greater Sage-Grouse sample, which spanned the southern half of the range. Thus, we provide much stronger genetic evidence supporting the recognition of Gunnison Sage-Grouse as a distinct species with low genetic diversity. Further, our work confirms that the Bi-State population is differentiated from other Greater Sage-Grouse. The level of differentiation is much less than the divergence between Greater and Gunnison sage-grouse, supporting the idea that the Bi-State represents a unique population within the Greater Sage-Grouse. New genomic methods like the restriction-site-associated DNA (RAD-tag) method used here illustrate how increasing the number of markers and coverage of the genome can better characterize patterns of genetic variation, particularly among recently diverged taxa, providing vital information for conservation and management.